2021
DOI: 10.3389/fpubh.2021.766972
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Behaviors and Suicide-Related Behaviors in Adolescents: Cross-Sectional Study Using the 2019 YRBS Data

Abstract: Objective: The purpose of this research was to investigate the prevalence of lifestyle behaviors and suicide-related behaviors and the association between them using a nationally representative sample of adolescents from the USA.Methods: 13,677 high school students aged 14-18 years were included in this cross-sectional study. The research data were retrieved from the Youth Risk Behavior Surveillance System Survey in 2019. All data on age, sex, grade, race, physical activity, television time, fruit intake, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 42 publications
(48 reference statements)
0
20
1
Order By: Relevance
“…Another study conducted by Li et al reported a reverse link between exercise and suicide plan in American high school students. The results showed that students who never did exercise had approximately 1.31 greater times risk of suicide plan compared to those more frequently engaged in exercise [ 23 ]. Although there was not enough evidence on answering the mechanism of association between exercise and suicide-related behaviors, several potential explanations may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Li et al reported a reverse link between exercise and suicide plan in American high school students. The results showed that students who never did exercise had approximately 1.31 greater times risk of suicide plan compared to those more frequently engaged in exercise [ 23 ]. Although there was not enough evidence on answering the mechanism of association between exercise and suicide-related behaviors, several potential explanations may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al [ 21 ], taking advantage of the data from the YRBS in 2019, found that skipping breakfast totally was associated with increased risk of suicidal ideation (OR:1.39, 95%CI: 1.41–1.71), suicide plan (OR: 1.49, 95%CI: 1.12–1.98), and suicide attempt (OR: 1.64, 95%CI: 1.18–2.27). In this study, we used the data of the YRBSs from 2011 to 2019 and found that skipping breakfast was also related to medically serious suicide attempt.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that intervention for breakfast skipping is necessary in the education of dietary behaviors among adolescents. Although previous studies [ 21 , 22 ] have tended to summarize breakfast consumption into lifestyle behaviors in order to explore the association with suicidality, breakfast consumption itself—as an indispensable meal and a source of nutrients—might play an important role in nutritious factors, and therefore should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations